ANALISIS PENGENDALIAN PERSEDIAAN BAWANG MERAH VARIETAS BREBES DAN SUMENEP DI AGROINDUSTRI BAWANG GORENG DUA SAUDARA KECAMATAN CIOMAS KABUPATEN BOGOR - Pradila, Ulfa Devi; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Lampung University, 2024)
This research aims to analyze the most economical quantity of orders for raw materials, calculate the amount of safety stock, the reorder point, and the total inventory costs. The analytical method used is quantitative analysis with the probabilistic EOQ method. The research was carried out using a case study method at the Bawang Goreng Dua Saudara Agroindustry. The research location was deliberately chosen. Respondents in the research consisted of agroindustry owners and workers. The research results show that the most economical order for brebes shallots using the probabilistic EOQ method is 7.646 kg per order, and the most economical order quantity for sumenep shallots is 4.442 kg per order. There is a total savings in inventory costs using the probabilistic EOQ method of IDR 1.439.008 (9%) for brebes shallots and IDR 62.398 (1%) for sumenep shallots. Brebes shallots must be ordered when the reorder point value is 6.817 kg and the amount of safety stock is 2.918 kg. Meanwhile, sumenep shallots should be ordered with a reorder point value of 3.167 kg, and the amount of safety stock that must be available is 125 kg. Keywords: agroindustry, probabilistic EOQ, raw materials, shallots